Uncovering the hidden mineral treasure of the Jurassic Younger Granite region of Nigeria using integrated magnetic geophysical techniques - Usman, Ayatu Ojonugwa; Nomeh, Joseph Sunday; Abraham, Ema Michael; Azuoko, George-Best (Frontiers in Earth Science, 2025)
The Jurassic Younger Granite (JYG) Province in Nigeria is notable for its rich mineral resources, though much of its subsurface wealth remains unexplored. This study utilizes integrated magnetic geophysical techniques to assess the region’s concealed mineral potential. High-resolution aeromagnetic data was employed to map geologic structures, lithological variations, and zones of mineralization. Advanced filtering methods, including reduce to magnetic equator (RTME), Butterworth bandpass filter, analytical signal (AS), tilt derivative (TRD), and first vertical derivative (FVD), alongside depth estimation tools like source parameter imaging (SPI), Euler deconvolution, and 3D magnetic inversion, were used to uncover new mineralization patterns. Magnetic anomaly maps reveal variations in magnetic intensity, indicating rock bodies with differing magnetic properties. The RTME map shows deeply seated deformations, while TRD and Rose diagram analysis identify NE-SW and minor E-W fault and fold trends related to Pan-African orogeny. FVD and phase symmetry analysis indicate granitic rock intrusions, contributing to intense faulting and folding. The AS map highlights minor magnetic irregularities tied to deposits of tin, columbite, and monazite. Depth estimations using SPI indicate shallow magnetic sources, concentrated in the central and northwestern regions. Euler deconvolution, with a structural index of 0, identifies clusters of solutions interpreted as dykes and sills at depths of 100–300 m, with E-W trending structures. 3D inversion model reveals evidence of geologic structures that can host appreciable mineral deposits in the region. These results demonstrate a strong correlation between magnetic anomalies and known mineral deposits, suggesting further untapped resources. This integrated approach highlights the effectiveness of magnetic geophysical techniques in mineral exploration and offers a foundation for similar studies in comparable geological settings.